Análise de anabolizantes apreendidos no Brasil por espectrometria de massas com ionização por paper spray e métodos quimiométricos - Ana Gabriella Carvalho Miguita (2018)
Drug counterfeiting has been a concern of health agencies for years, due to health problems that can be caused, such as allergic reactions and side effects, which can even lead to death. In Brazil, the most recent data on drug seizures by the Brazilian Police (from 2006 to 2011) show that anabolic steroids were the second largest seized class, behind only the drugs for erectile dysfunction. Therefore, the main objective of this work was to evaluate the use of paper spray mass spectrometry (PS-MS) together with chemometric methods to analyze seized anabolic samples. A total of 75 samples in tablet, oil and suspension forms, the last two in the injectable forms, were selected for this work, resulting from seizures carried out by the Polícia Civil de Minas Gerais and by the Federal Polices of Minas Gerais and Brasília. All samples were analyzed by PS-MS in the positive mode, the mass range 50 1000 m/z, resulting in spectra containing peaks related to the respective active principles contained in each sample. Principal component analysis (PCA) was thenperformed primarily for the samples in tablet and suspension forms andsubsequently on the oily samples, for which a trand was observed for theseparation of the samples according to the active principles present, being possible to detect cases of adulteration. The method of ordered predictor selection (OPS) was used in the exploratory model for the oily samples in order to improve the separation of the clusters with a reduced number of selective spectral variables. In this model, samples were clustered according two active principles present using 28 variables and describing 69.82% of the variance, with 3 principal components.